Heterogeneous photocatalytic cyanomethylarylation of alkenes with acetonitrile: synthesis of diverse nitrogenous heterocyclic compounds - Pan, Guanglong; Yang, Qian; Wang, Wentao; Tang, Yurong; Cai, Yunfei (Beilstein Journal of Organic Chemistry, 2021)
A visible light-mediated heterogeneous photocatalytic cyanomethylarylation of alkenes with acetonitrile has been established using K-modified carbon nitride (CN-K) as a recyclable semiconductor photocatalyst. This protocol, employing readily accessible alkyl N-hydroxyphthalimide (NHPI) ester as a radical initiator, allows the efficient construction of a broad array of structural diverse nitrogenous heterocyclic compounds including indolines, oxindoles, isoquinolinones, and isoquinolinediones.
Keywords: carbon nitride; cyanoalkylarylation; heterocyclic compound; heterogeneous photocatalysis; recyclable

(untitled) - Newhouse, T.; Baran, P. S. (J. Am. Chem. Soc., 2008)

(untitled) - Mohn, T.; Plitzko, I.; Hamburger, M. (Phytochemistry, 2009)

(untitled) - Zhang, D.; Song, H.; Qin, Y. (Acc. Chem. Res., 2011)

(untitled) - Matsuura, T.; Overman, L. E.; Poon, D. J. (J. Am. Chem. Soc., 1998)

(untitled) - Marti, C.; Carreira, E. M. (Eur. J. Org. Chem., 2003)

(untitled) - Jiang, T.; Kuhen, K. L.; Wolff, K.; Yin, H.; Bieza, K.; Caldwell, J.; Bursulaya, B.; Tuntland, T.; Zhang, K.; Karanewsky, D.; He, Y. (Bioorg. Med. Chem. Lett., 2006)

(untitled) - Singh, G. S.; Desta, Z. Y. (Chem. Rev., 2012)

(untitled) - Scott, J. D.; Williams, R. M. (Chem. Rev., 2002)

(untitled) - Kaila, N.; Follows, B.; Leung, L.; Thomason, J.; Huang, A.; Moretto, A.; Janz, K.; Lowe, M.; Mansour, T. S.; Hubeau, C.; Page, K.; Morgan, P.; et al. (J. Med. Chem., 2014)

(untitled) - Hekal, M. H.; Abu El‐Azm, F. S. M.; Sallam, H. A. (J. Heterocycl. Chem., 2019)

(untitled) - Billamboz, M.; Bailly, F.; Barreca, M. L.; De Luca, L.; Mouscadet, J.-F.; Calmels, C.; Andréola, M.-L.; Witvrouw, M.; Christ, F.; Debyser, Z.; Cotelle, P. (J. Med. Chem., 2008)

(untitled) - Billamboz, M.; Bailly, F.; Lion, C.; Touati, N.; Vezin, H.; Calmels, C.; Andréola, M.-L.; Christ, F.; Debyser, Z.; Cotelle, P. (J. Med. Chem., 2011)

(untitled) - Girard, S. A.; Knauber, T.; Li, C.-J. (Angew. Chem., Int. Ed., 2014)

(untitled) - López, R.; Palomo, C. (Angew. Chem., Int. Ed., 2015)

(untitled) - Song, R.-J.; Liu, Y.; Xie, Y.-X.; Li, J.-H. (Synthesis, 2015)

(untitled) - Li, C.-C.; Yang, S.-D. (Org. Biomol. Chem., 2016)

(untitled) - Chu, X.-Q.; Ge, D.; Shen, Z.-L.; Loh, T.-P. (ACS Catal., 2018)

(untitled) - Wu, T.; Mu, X.; Liu, G. (Angew. Chem., Int. Ed., 2011)

(untitled) - Li, J.; Wang, Z.; Wu, N.; Gao, G.; You, J. (Chem. Commun., 2014)

(untitled) - Pan, C.; Zhang, H.; Zhu, C. (Org. Biomol. Chem., 2015)

(untitled) - Li, X.; Xu, J.; Gao, Y.; Fang, H.; Tang, G.; Zhao, Y. (J. Org. Chem., 2015)

(untitled) - Tang, S.; Li, S.-H.; Li, Z.-H.; Zhou, D.; Sheng, R.-L. (Tetrahedron Lett., 2015)

(untitled) - Ni, Z.; Huang, X.; Wang, J.; Pan, Y. (RSC Adv., 2016)

(untitled) - Liang, D.; Song, X.; Xu, L.; Sun, Y.; Dong, Y.; Wang, B.; Li, W. (Tetrahedron, 2019)

(untitled) - Pan, C.; Wang, Y.; Wu, C.; Yu, J.-T. (Catal. Commun., 2019)

(untitled) - Zhang, H.; Chen, P.; Liu, G. (Synlett, 2012)

(untitled) - Chen, J.-R.; Hu, X.-Q.; Lu, L.-Q.; Xiao, W.-J. (Chem. Soc. Rev., 2016)

(untitled) - Marzo, L.; Pagire, S. K.; Reiser, O.; König, B. (Angew. Chem., Int. Ed., 2018)

(untitled) - Liu, Y.; Zhang, J.-L.; Song, R.-J.; Li, J.-H. (Org. Chem. Front., 2014)

(untitled) - Zhang, J.-L.; Liu, Y.; Song, R.-J.; Jiang, G.-F.; Li, J.-H. (Synlett, 2014)

(untitled) - Lu, M.; Zhang, T.; Tan, D.; Chen, C.; Zhang, Y.; Huang, M.; Cai, S. (Adv. Synth. Catal., 2019)

(untitled) - Yang, Q.; Pan, G.; Wei, J.; Wang, W.; Tang, Y.; Cai, Y. (ACS Sustainable Chem. Eng., 2021)

(untitled) - Liu, X.; Fechler, N.; Antonietti, M. (Chem. Soc. Rev., 2013)

(untitled) - Wu, M.; Yan, J.-M.; Tang, X.-n.; Zhao, M.; Jiang, Q. (ChemSusChem, 2014)

(untitled) - Zhang, G.; Lin, L.; Li, G.; Zhang, Y.; Savateev, A.; Zafeiratos, S.; Wang, X.; Antonietti, M. (Angew. Chem., Int. Ed., 2018)

(untitled) - Xu, Y.; He, X.; Zhong, H.; Singh, D. J.; Zhang, L.; Wang, R. (Appl. Catal., B, 2019)

(untitled) - Lang, X.; Chen, X.; Zhao, J. (Chem. Soc. Rev., 2014)

(untitled) - Friedmann, D.; Hakki, A.; Kim, H.; Choi, W.; Bahnemann, D. (Green Chem., 2016)

(untitled) - Chen, J.; Cen, J.; Xu, X.; Li, X. (Catal. Sci. Technol., 2016)

(untitled) - Savateev, A.; Antonietti, M. (ACS Catal., 2018)

(untitled) - Savateev, A.; Ghosh, I.; König, B.; Antonietti, M. (Angew. Chem., Int. Ed., 2018)

(untitled) - Zheng, Y.; Lin, L.; Wang, B.; Wang, X. (Angew. Chem., Int. Ed., 2015)

(untitled) - Markushyna, Y.; Smith, C. A.; Savateev, A. (Eur. J. Org. Chem., 2020)

(untitled) - Cai, Y.; Tang, Y.; Fan, L.; Lefebvre, Q.; Hou, H.; Rueping, M. (ACS Catal., 2018)

(untitled) - Geng, P.; Tang, Y.; Pan, G.; Wang, W.; Hu, J.; Cai, Y. (Green Chem., 2019)

(untitled) - Kurpil, B.; Otte, K.; Mishchenko, A.; Lamagni, P.; Lipiński, W.; Lock, N.; Antonietti, M.; Savateev, A. (Nat. Commun., 2019)

(untitled) - Markushyna, Y.; Teutloff, C.; Kurpil, B.; Cruz, D.; Lauermann, I.; Zhao, Y.; Antonietti, M.; Savateev, A. (Appl. Catal., B, 2019)

(untitled) - Mazzanti, S.; Kurpil, B.; Pieber, B.; Antonietti, M.; Savateev, A. (Nat. Commun., 2020)

(untitled) - Yang, C.; Li, R.; Zhang, K. A. I.; Lin, W.; Landfester, K.; Wang, X. (Nat. Commun., 2020)

(untitled) - Wang, J.; Xue, L.; Hong, M.; Ni, B.; Niu, T. (Green Chem., 2020)

(untitled) - Wen, J.; Yang, X.; Sun, Z.; Yang, J.; Han, P.; Liu, Q.; Dong, H.; Gu, M.; Huang, L.; Wang, H. (Green Chem., 2020)

(untitled) - Ghosh, I.; Khamrai, J.; Savateev, A.; Shlapakov, N.; Antonietti, M.; König, B. (Science, 2019)

(untitled) - Pieber, B.; Malik, J. A.; Cavedon, C.; Gisbertz, S.; Savateev, A.; Cruz, D.; Heil, T.; Zhang, G.; Seeberger, P. H. (Angew. Chem., Int. Ed., 2019)

(untitled) - Cavedon, C.; Madani, A.; Seeberger, P. H.; Pieber, B. (Org. Lett., 2019)

(untitled) - Khamrai, J.; Ghosh, I.; Savateev, A.; Antonietti, M.; König, B. (ACS Catal., 2020)

(untitled) - Qin, Y.; Martindale, B. C. M.; Sun, R.; Rieth, A. J.; Nocera, D. G. (Chem. Sci., 2020)

(untitled) - Slutskyy, Y.; Overman, L. E. (Org. Lett., 2016)

(untitled) - Jin, Y.; Yang, H.; Fu, H. (Org. Lett., 2016)

(untitled) - Wang, G.-Z.; Shang, R.; Fu, Y. (Org. Lett., 2018)

(untitled) - Tang, Q.; Liu, X.; Liu, S.; Xie, H.; Liu, W.; Zeng, J.; Cheng, P. (RSC Adv., 2015)

(untitled) - Kachkovskyi, G.; Faderl, C.; Reiser, O. (Adv. Synth. Catal., 2013)